(untitled) (Journal of Environmental Science and Natural Resources, 2019)
The study was conducted to assess the effect of formulated feed on the growth performance of prawn both in aquarium and pond system during 25 September to 25 December 2013. The feeds/diets were, diet 1 (formulated feed), diet 2 (commercial feed), diet 3 (custard cake) and diet 4 (shuji-ata ball). Protein percent of the feeds were 34.51% in Diet-1, 32.67% in Diet-2, 25.41% in Diet-3 and 21.43% in Diet 4. Four experimental diets were assigned to four treatments viz. T1, T2, T3 and T4 both in aquarium and pond. The water quality parameters were monitored 15 days interval and the ranges were: temperature 26°C to 29.8°C (aquarium system) and 24.5°C to 29.9°C (pond system) ; pH 7.07 to 8.09 (aquarium system) and 7.87 to 8.45 (pond system); DO 7.07 to 8.09 (aquarium system) and 5.08 to 5.86 mg/L (pond system). The result of the present study showed that Prawn feed Diet 1 and Diet 2 resulted highest weight gain 2.42 and 2.39 g (aquarium system) and 3.63 and 3.5g (pond system), respectively. Based on the result of present study, it could be suggested that shrimp waste can be replaced in the diets of prawn (Macrobrachium rosenbergii) along with other ingredients. J. Environ. Sci. & Natural Resources, 11(1-2): 59-71 2018